Rehabilitation of patients with rheumatoid arthritis treated in stationary spa treatment (Journal of Health Sciences, 2015)
Introduction: Rheumatic diseases are nonsurgical diseases of the locomotor system and connective tissue. Rheumatoid arthritis (RA) is a systemic inflammatory disease of connective tissue of unknown cause, with progressive chronic or subacute course. The aim of the research is to determine whether stationary spa treatment leads to improvement of the functional status in patients with rheumatoid arthritis. Methods: We included 35 patients with diagnosis of rheumatoid arthritis, referred for treatment at the spa " Ilidža " Gradačac from February to April 2014. Patients not adhering to treatment protocols were excluded. We used Visual analogue pain scale (VAS), HAQ questionnaire and assessment of the clinical condition before and after the treatment based on the scores 1-5.Results: There were 32 female and 3 male patients. The average age was 62.28±8.31 years. Based on the HAQ, 12 patients had no difficulties, 9 of them perform activities with little difficulties, 10 with many difficulties, and 4 patients cannot perform certain activities. Before treatment VAS was 6.63±2.36, and after treatment the 2.51±2.27. Ratings of clinical condition before treatment was 2.38±0.74, and after the treatment 3.64±0.98. The most frequently used therapies were kinesitherapy, magnetotherapy and interferential electricity. Conclusions: Stationary treatment at the spa „Ilidža“ Gradačac leads to an improvement of the functional status in patients with rheumatoid arthritis.